2009
DOI: 10.1159/000191199
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Kidney Function Decline in the Last Year prior to Dialysis

Abstract: Background: Establishing a comprehensive characterization of kidney function decline before dialysis is necessary to predict dialysis onset and prepare patients for replacement therapy. Aims: To investigate kidney function as measured by pattern and rate of decline in glomerular filtration rate (GFR) over the year preceding dialysis and to identify factors associated with a nonlinear GFR decline. Methods: We enrolled patients beginning dialysis in Lorraine (France) in 2005 and 2006, who were referred to a neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Patients with polycystic kidney disease may have less RFT variability, while patients with cardiovascular disease may be more likely to have nonlinear RFT. 18 Although diabetics are assumed to have faster RFT declines, similar RFTs are seen in diabetics and nondiabetics at comparable levels of albuminuria. 19 Patients with eGFR >60 ml/min/1.73 m 2 may have greater RFT variability and may need mGFR to assess renal function changes over time.…”
Section: Subjects To Include In Trials and Matching Of Rftrelated Facmentioning
confidence: 99%
“…Patients with polycystic kidney disease may have less RFT variability, while patients with cardiovascular disease may be more likely to have nonlinear RFT. 18 Although diabetics are assumed to have faster RFT declines, similar RFTs are seen in diabetics and nondiabetics at comparable levels of albuminuria. 19 Patients with eGFR >60 ml/min/1.73 m 2 may have greater RFT variability and may need mGFR to assess renal function changes over time.…”
Section: Subjects To Include In Trials and Matching Of Rftrelated Facmentioning
confidence: 99%
“…Patients with a slower trajectory (BT <3 ml/min/1.73 m 2 /year) may require less intensive follow-up [81]. On the other hand, in one study, almost half of the patients had a nonlinear decline in renal function in the year prior to dialysis initiation [82]. A difference in rate of eGFR decline per year of 1 ml/min/1.73 m 2 can have a very powerful effect on the timeframe to start RRT.…”
Section: Using Trajectory In Clinical Decisionsmentioning
confidence: 99%
“…Given the convenience of assuming a linear GFR trajectory, which results from the ease of modeling and interpreting linear slopes, few studies have sought to validate the linearity assumption and explore the possibility of nonlinear GFR decline. However, nonlinearity in GFR decline has been observed in some epidemiologic studies, [5][6][7] and the implications on the risk for adverse outcomes have generated interest. 8 A CKD cohort study in France found that about one half of its patients experienced nonlinear GFR decline during the last year before dialysis.…”
mentioning
confidence: 99%
“…8 A CKD cohort study in France found that about one half of its patients experienced nonlinear GFR decline during the last year before dialysis. 5 A study by Li et al 9 used a flexible approach to model nonlinearity in GFR trajectories. Li et al 9 found evidence of nonlinear GFR trajectory behavior in adult patients with CKD, and furthermore, the probability of having nonlinear features in an individual trajectory was associated with known risk factors for CKD progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation